2009
DOI: 10.1007/s10545-009-1149-1
|View full text |Cite
|
Sign up to set email alerts
|

Sensory integration intervention: Historical concepts, treatment strategies and clinical experiences in three patients with succinic semialdehyde dehydrogenase (SSADH) deficiency

Abstract: This paper is a review of clinical experiences providing developmental therapy services for three boys diagnosed with paediatric neurotransmitter disease. The clinical presentation of paediatric neurotransmitter diseases might parallel other diagnostic characteristics seen in a typical paediatric therapy clinic (i.e. hypotonia, motor and cognitive delays, coordination, expressive speech, and ocular motor difficulties.) From the clinical perspective of the author, sensory integrative function is but one aspect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Case ascertainment dating back to the initial report of gamma-hydroxybutyric aciduria identified 91 unique patients with clinical details provided (Aoshima et al 2002;Bekri et al 2004;Brown et al 1987;Dayan et al 2006;Deng et al 2011;Divry et al 1983;Escalera et al 2010;Gogou et al 2016;Haan et al 1985; Ishiguro et al 2001; Jakobs et al 1981;Jiang et al 2013;Kratz 2009;Kwok et al 2012;Lemes et al 2006;Li et al 2015;Lin et al 2015;Liu et al 2016;Neu et al 2002;Niemi et al 2014;O'Rourke et al 2010;Onkenhout et al 1989;Pearl et al 2003;Peters et al 1999;Puttmann et al 2013;Racaru et al 2010;Rashed et al 1994;Rating et al 1984;Saronwala et al 2008;Spilioti et al 2013;Tay et al 2015;Wang et al 2016;Yamakawa et al 2012;Zhao et al 2003;Ziyeh et al 2002). We furthermore identified 91 additional subjects with confirmed SSADH deficiency in our database published in aggregate (Parviz et al 2014).…”
Section: Case Reports and Resultsmentioning
confidence: 99%
“…Case ascertainment dating back to the initial report of gamma-hydroxybutyric aciduria identified 91 unique patients with clinical details provided (Aoshima et al 2002;Bekri et al 2004;Brown et al 1987;Dayan et al 2006;Deng et al 2011;Divry et al 1983;Escalera et al 2010;Gogou et al 2016;Haan et al 1985; Ishiguro et al 2001; Jakobs et al 1981;Jiang et al 2013;Kratz 2009;Kwok et al 2012;Lemes et al 2006;Li et al 2015;Lin et al 2015;Liu et al 2016;Neu et al 2002;Niemi et al 2014;O'Rourke et al 2010;Onkenhout et al 1989;Pearl et al 2003;Peters et al 1999;Puttmann et al 2013;Racaru et al 2010;Rashed et al 1994;Rating et al 1984;Saronwala et al 2008;Spilioti et al 2013;Tay et al 2015;Wang et al 2016;Yamakawa et al 2012;Zhao et al 2003;Ziyeh et al 2002). We furthermore identified 91 additional subjects with confirmed SSADH deficiency in our database published in aggregate (Parviz et al 2014).…”
Section: Case Reports and Resultsmentioning
confidence: 99%
“…Conventional treatment for SSADHD relies on symptomatic relief (mainly in the form of pharmacologic seizure control [ 21 , 22 , 23 , 24 ]) and behavioral therapies customized toward specific symptoms and patient needs (movement disorders, speech delay, etc.) [ 13 , 21 , 24 , 25 , 26 ]. However, therapies that target the underlying enzyme deficiency in the form of gene therapy or ERT are non-existent to date.…”
Section: A Brief History and Update On Ssadhd Researchmentioning
confidence: 99%
“…In conclusion, there is no doubt that the GABA shunt is imperative for health, and its impairment triggers the development of several disease phenotypes, most of which are related to neurological disturbances [13,14,[76][77][78][79]. In this study, we showed that the GABA shunt is a promising route involved in the mitochondrial redox metabolism of cortical and hypothalamic synaptosomes and is linked to glucose metabolism by increasing HK activity at the mitochondrial level.…”
Section: Discussionmentioning
confidence: 62%